Values and labor force participation in the Nordic countries - Axel Hall; Gylfi Zoega (Kiel Institute for the World Economy (IfW), 2014)
The Nordic countries are known for their success in combining an extensive welfare state with high labor force participation. This is explained by the origins of their welfare states that can be traced to a unique set of values and beliefs that emphasize the right of women to participate in the labor market. These values are currently shared by individuals born in other European countries of Nordic parents. Some possible causal explanations are proposed.
Keywords: J21; J22; 330; employment; taxes; values; beliefs